EPC Minutes 2004-09-02 - Academic Senate:::::::::
Educational Policies Committee. Chair Report. Agenda – Approved. Minutes of 5/20/2021 – Approved. Consent item: Faculty Eligible for Emeritus Status – Approved. Information Items: Proposal for Leadership Development; Resolution of No Confidence in Library Dean; Faculty Services through Academic Personnel. President Report. Provost Report. Crash Course in Robert's Rules. Resolution Endorsing Joint Statement on Legislative Efforts to Restrict Education about Racism and American History- First Reading completed. Vice Chair Report. Vice President of Administration and Finance Report. Vice President for Student Affairs Report. Associated Students Report. Statewide Senator Report. APARC Report. Group Photo. EPC Report. FSAC Report. SAC Report. CFA Report. Occasional Report: GIG. Good of the Order.